(untitled) (Comparative & International Education Series, 2021)
The outbreak of COVID-19 has led to restrictions on access to face-to-face classes in schools and post-secondary institutions across the globe. As people seek online means to pursue learning opportunities, Learning Management Systems (LMSs) are becoming increasingly important. LMSs have traditionally relied on asynchronous methods to communicate with learners, such as email, bulletin boards, and blogs. These tools have also been used to facilitate student assessment such as the collection of assignments and the delivery of assessment feedback. However, certain types of summative assessments cannot be accomplished online using asynchronous tools. Observations, interviews, and proctored exams require a more synchronous approach to be considered valid in an online learning environment. Through a reflective lens, this chapter explores the case for incorporating synchronous tools such as video conferencing and live chat into online testing strategies to improve assessment validity in Technical Vocational Education and Training institutions.